A wireless "Janus" soft gripper with multiple tactile sensors. Issue 22 (13th October 2022) - Han, Lei; Wang, Rui; Dong, Yupeng; Zhang, Xun; Wu, Chenggen; Zhao, Xiaoguang
Abstract : We propose a fully flexible gripper integrated with pressure and material sensors. The sensing information can be wirelessly transmitted to the processor for analysis to acquire tactile information. Abstract : Biomimetic properties allow soft robots to complexly interact with the environment. As the bridge between the robot and the operating object, the gripping hand is an important organ for its connection with the outside world, which requires the ability to provide feedback from the grasped object, similar to the human sensory and nervous system. In this work, to cope with the difficulty of integrating complex sensing and communication systems into flexible soft grippers, we propose a GO/PI composite bilayer film-based gripper with two types of tactile sensors and a LC passive wireless transmission module to obtain the grip information and transmit it to the processor. The bilayer film structure demonstrates good photothermal driving performance. Pressure and material sensors are located at the tips of the gripper's fingers to acquire tactile information which is wirelessly transmitted to the processor for analysis via the LC circuit. The grasping and feedback of the gripper are presented through an intelligent display system, realizing the wireless interconnection between the robot terminal and processing system, exhibiting broad application potential.